A Critique of Preindustrial Communities, or An Anatomy of Pre-Modern World - Abbas Khalaji (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is an analytical-critical review of “Preindustrial Communities, or An Anatomy of Pre-Modern World” by Patricia Crone. This study is mainly concerned with the theoretical aspect and the content of the book. Hence, the scientific method, theoretical approach, and historical data, and the content analysis of the book are evaluated, and its strengths, and shortcomings are identified. Accordingly, the critical phase of this study is presented in three sections relating to form, methodology, and content. The strong points of the book relate to the fact that the author retains powerful imagination, precise visualization, interpretive analysis of the preindustrial situation, and the ability to illustrate the cultural, political, social, and economic situations of pre-modern era with an accurate explanation of the positions of politics, government, culture, society, individuals, and religion.